2010
DOI: 10.1373/clinchem.2010.144121
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNA 499 as a Biomarker of Acute Myocardial Infarction

Abstract: BACKGROUND: MicroRNAs (miRNAs) are endogenous small RNAs 21-25 nucleotides in length. Recently, we reported that miRNA 208 (miR-208) is produced exclusively in the rat myocardium and that plasma miR-208 is a biomarker of myocardial injury in rats. In the present study, we assessed the hypothesis that plasma concentrations of myocardial-specific miRNAs can be used to diagnose myocardial injury in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
285
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(306 citation statements)
references
References 16 publications
14
285
1
6
Order By: Relevance
“…Following blasticidin selection, cultures were maintained in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum for the duration of the cultures. On days 0, 3,7,10,14,20,28,35,45,60,90, and 120, approximately 3 million cells were removed for RNA collection. The differentiation protocol and sample collection were performed in 3 independent replicates as indicated by Run 1, 2, and 3 in Figs.…”
Section: Cardiomyocyte Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following blasticidin selection, cultures were maintained in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum for the duration of the cultures. On days 0, 3,7,10,14,20,28,35,45,60,90, and 120, approximately 3 million cells were removed for RNA collection. The differentiation protocol and sample collection were performed in 3 independent replicates as indicated by Run 1, 2, and 3 in Figs.…”
Section: Cardiomyocyte Differentiationmentioning
confidence: 99%
“…S3). Finally, the expression pattern of miRNAs previously shown to be important in heart development and disease was examined: developmentally regulated miR-1, miR-133a, miR-133b, miR-208a, miR-208b, miR-143, and miR-145 [8]; hypertrophy-associated miR-199a and miR-214 [44]; and a circulating serum biomarker of human myocardial infarction, miR-499 [45,46]. These miRNAs all followed the predicted patterns given their roles in cardiomyocyte function, disease, and development (Fig.…”
Section: Mirna Profiling During Hipsc Differentiationmentioning
confidence: 99%
“…Further to this, the role of miR-499 in AMI diagnosis has been supported by Adachi et al in which they measured the plasma concentration of miR-499 in 14 patients with acute coronary syndrome, 15 patients with congestive heart failure (CHF) and 10 patients without any cardiovascular disease. They concluded that miR-499 was exclusive to cardiac tissue with significant increase in plasma level following acute myocardial infarction (AMI) than below the limit of detectable range in plasma with other groups mentioned above [61].…”
Section: S Pokhrel Y Guotian World Journal Of Cardiovascular Diseasesmentioning
confidence: 94%
“…There was an increase of more than 1,000-fold in acute myocardial infarction 6,[37][38][39] of miRs-208b and-499. In this condition, they reflect tissue injury and cell death.…”
Section: Microrna As Biomarker In Heart Failurementioning
confidence: 96%